2023
DOI: 10.3389/fanim.2023.1093857
|View full text |Cite
|
Sign up to set email alerts
|

An automated system for cattle reproductive management under the IoT framework. Part II: Induction of luteinizing hormone release after gonadotropin releasing hormone analogue delivery with e-Synch

Abstract: Technologies for automating animal management and monitoring tasks can improve efficiency and productivity of livestock production. We developed the e-Synch system for automated control and monitoring the estrous cycle of cattle through intravaginal hormone delivery and sensing. Thus, our objective was to evaluate luteinizing hormone (LH) concentrations after intravaginal instillation of the Gonadotropin-releasing hormone (GnRH) analogue Gonadorelin with the e-Synch system. This system consists of an intravagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 30 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…Conversely, all hormone reservoirs in all other devices in both experiments were completely empty suggesting that all fluid was released during insertion. Hormone solution release was also confirmed based on the physiological response observed in both experiments as described in the companion manuscript (Ren et al, 2023). This was more evident for cows that received a GnRH dose and volume of solution that caused an increase in circulating concentrations of LH above baseline.…”
Section: System Performancementioning
confidence: 58%
See 4 more Smart Citations
“…Conversely, all hormone reservoirs in all other devices in both experiments were completely empty suggesting that all fluid was released during insertion. Hormone solution release was also confirmed based on the physiological response observed in both experiments as described in the companion manuscript (Ren et al, 2023). This was more evident for cows that received a GnRH dose and volume of solution that caused an increase in circulating concentrations of LH above baseline.…”
Section: System Performancementioning
confidence: 58%
“…Our in vivo experiments with dairy cows demonstrated that the current e-Synch system could be successfully programmed to deliver hormone solutions in a timely manner. Programmed hormone release was evidenced by the absence of fluid residue after device disassemble and the temporal dynamic of LH concentrations for cows that received GnRH in Exp 2 (Ren et al, 2023). Cows that received the high dose of GnRH had an LH surge of at least similar magnitude and timing than that of cows that received GnRH by i.m.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations